Technological platforms in the field of Earth sciences — a response to challenges of the XXIst century - Zagorodnyuk, P. A.; Ivanova, E. N.; Liventseva, A. A. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2018)
Technological platforms in the field of Earth sciences are qualitatively new models of balanced and high-yielding business on effective use of natural resources. Taking as an example the functioning of the platform “Introduction in Ukraine the standards of European Union on effective and balanced usage of energetic, mineral, water and land resources” elaborated by the specialists of the International hub of natural resources TUTKOVSKY and contributed at the VI Congress of the geologists of Ukraine, the expediency of establishment of such interaction of state, sociability and business has been proved. The International hub of natural resources TUTKOVSKY is an operational center of the wide net of enterprises-partners, which integrate the interests of service and products suppliers and their consumers: investors, manufacturing companies and governments realizing the projects on the usage of natural resources in different countries of the world. TUTKOVSKY successively organizes a system networked cooperation to integrate the experience and manufacturing capacities of separate enterprises, progression of their high-tech production and services to meet the demands of their consumers.